Analisis tingkat pendapatan masyarakat dalam perspektif ekonomi islam pada lingkungan sosial berbasis ma: (Studi kasus Desa Balearjosari, Perumahan Riverside Rw 05) - Afifah, Diah Ayu (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the level of community income and its relationship with the practice of almsgiving (sedekah) from the perspective of Islamic economics within a mosque-based social environment. The research was conducted in Riverside Housing Area RW 5 using a case study approach during the implementation of the Community Service Program (Kuliah Kerja Nyata/KKN). The research method employed was descriptive qualitative, with data collected through observation, interviews, and documentation of the community surrounding the mosque. The results show that the community of Riverside RW 5 has an income level classified as middle to upper-middle and high, influenced by the dominance of professional occupations such as doctors, lecturers, teachers, lawyers, and tax accountants. This stable and relatively high income level has a positive impact on the community’s economic welfare and increases social participation, particularly in religious activities and mosque-based almsgiving practices. Almsgiving is carried out actively and continuously in various mosque activities, such as weekly religious studies and gatherings, in the form of food provision and other types of social assistance. From the perspective of Islamic economics, the practice of almsgiving reflects the implementation of the principle of balance between wealth ownership and social responsibility. Wealth is viewed as a trust (amanah) that must be managed and distributed for the benefit of the community through Islamic philanthropic instruments. The mosque plays an important role as a center for the distribution of almsgiving as well as a means of strengthening social solidarity and Islamic brotherhood (ukhuwah Islamiyah). Therefore, this study indicates that a good level of income, when accompanied by strong religious values, can encourage economic behavior oriented toward social justice and collective welfare in accordance with the principles of Islamic economics. The results show that the community of Riverside RW 5 has an income level classified as middle to upper-middle and high, influenced by the dominance of professional occupations such as doctors, lecturers, teachers, lawyers, and tax accountants. This stable and relatively high income level has a positive impact on the community’s economic welfare and increases social participation, particularly in religious activities and mosque-based almsgiving practices. Almsgiving is carried out actively and continuously in various mosque activities, such as weekly religious studies and gatherings, in the form of food provision and other types of social assistance. From the perspective of Islamic economics, the practice of almsgiving reflects the implementation of the principle of balance between wealth ownership and social responsibility. Wealth is viewed as a trust (amanah) that must be managed and distributed for the benefit of the community through Islamic philanthropic instruments. The mosque plays an important role as a center for the distribution of almsgiving as well as a means of strengthening social solidarity and Islamic brotherhood (ukhuwah Islamiyah). Therefore, this study indicates that a good level of income, when accompanied by strong religious values, can encourage economic behavior oriented toward social justice and collective welfare in accordance with the principles of Islamic economics.